2016
DOI: 10.7752/jpes.2016.04185
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Purpose and materials: This article presents an analysis of the competitive level training of young Russian judo contestants (18 to 20 years old) who represent the Krasnoyarsk territory and the Siberian Federal District. The invited experts (i.e., judges and coaches) analysed competition battles of a number of athletes. The experts focused on the number of faults (shido), the number of real attempts at applying techniques either from a standing position (Nage-waza) or on the ground (Ne-waza), the number of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
0
6
0
3
Order By: Relevance
“…Since these loads are not typical for the wrestling match athletes training in the training program for sports combatants show significantly lower recovery rates after loads than athletes using intensive functional training techniquescrossfit. According to experts, a significant shortage of modern and effective functional training techniques can be observed today in many martial artists (Osipov, Kudryavtsev, Struchkov, et al, 2016). It should be noted that the use of methods of functional training -crossfit will allow fighters not only to increase the level of functional readiness but also to increase the level of development of other physical qualities, for example, strength.…”
Section: Discussionmentioning
confidence: 99%
“…Since these loads are not typical for the wrestling match athletes training in the training program for sports combatants show significantly lower recovery rates after loads than athletes using intensive functional training techniquescrossfit. According to experts, a significant shortage of modern and effective functional training techniques can be observed today in many martial artists (Osipov, Kudryavtsev, Struchkov, et al, 2016). It should be noted that the use of methods of functional training -crossfit will allow fighters not only to increase the level of functional readiness but also to increase the level of development of other physical qualities, for example, strength.…”
Section: Discussionmentioning
confidence: 99%
“…According to the experts, in modern judo, the success of an athlete in competitive activities can bring only a significant number of attacking technical actions more than the opponents [3,48]. It was revealed that high rates of motor abilities that determine the level of motor activity of the athletes during the fights are significantly correlated with the level of the athletic skill and sporting achievements of the judoists [55].…”
Section: Discussionmentioning
confidence: 99%
“…According to the experts, the Russian athletes were not fully prepared for the changes in the rules of judo [40,47]. First of all, the athletes could not maintain a high level of motor activity during the entire competition match [48]. Increasing the level of competitiveness of the Russian athletes as well as the athletes of the postSoviet space the authors of the article are directed.…”
Section: Introductionmentioning
confidence: 99%
“…What is more the specialists note that modern judo rules impose very high demands on the dynamics of conducting competitive bouts and encourage an active fight against a large number of technical actions (Osipov, Kudryavtsev, Struchkov, et al, 2016;Krstulović, Zuvela, Katić, 2006). In view of these conditions, the coaches build the process of training of the qualified judokas in such a way that their wards outperform their rivals in physical strength, speed and endurance (Osipov, Kudryavtsev, Kuzmin, et al, 2016;Manolachi, 2015;Drapsin, Drid, Grujic, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%